Zhipan's account of the history of Buddhism in China / Volume 3 Fozu tongji, juan 43-48: the Song dynasty / by Thomas Jülch - Zhipan (Zhipan's account of the history of Buddhism in China, 2023)
With his carefully annotated translation of Fozu tongji, juan 43-48, Thomas Jülch enables an in-depth understanding of a key text of Chinese Buddhist historiography